Feasibility Study on Performance of Heat Exchanger-001 Refinery in Pusat Pengembangan Sumber Daya Manusia MIGAS Cepu - E Saputro; R A Santoso; N N Saraswati; M Rochim (Biomedical and Mechanical Engineering Journal (BIOMEJ), 2022)
PPSDM Migas Cepu is one of the oil and gas industries in Indonesia. Their process requires Heat Exchanger for pre-heating purposes. The Heat Exchanger cannot work optimally because of the impurities attached to the walls shell and tube. Sometimes the impurities are attached to the walls of the shell and tube, so it makes can’t work optimally in this industry. For that reason, the purpose of this calculation is to find out the heat efficiency during the process. Heat efficiency is the ratio of the amount of heat that moves from a high-temperature fluid to a lower temperature fluid in a certain time unit which can show the performance of a Heat Exchanger. The result show that the clean overall coefficient (Uc) and design overall coefficient (Ud) are 7,4301 Btu/ft2.jam.oF and 7,2517 Btu/ft2.jam.oF. For dirt factor (Rd) are 0,0033 ft2.jamoF/Btu. The Pressure Drop is 0,0448 Psi for Tube and 0,0035 Psi for Shell. The value of the Heat Efficiency is 82,3840 %. This means according to the results of these parameters, it can be concluded that the Heat Exchanger-001 is still possible to operate.